Effectiveness of combined shockwave therapy and plantar fascia stretching interventions in treating plantar heel pain: a systematic review and meta-analysis protocol. Issue 5 (16th May 2021) - Burton, Ian; Cooper, Kay; Alexander, Lyndsay; Swinton, Paul Alan
ABSTRACT: Objective: The objective of this review is to synthesize the best available evidence on the effectiveness of interventions that have used a combination of extracorporeal shockwave therapy and plantar fascia–specific stretching to treat plantar heel pain compared to any other non-surgical intervention. Introduction: Recent evidence suggests combining shockwave therapy and plantar fascia stretching may be more effective than other treatments for plantar heel pain. However, no systematic reviews have been conducted on the topic and optimal treatment protocols and clinical recommendations are lacking. Inclusion criteria: Randomized controlled trials assessing the effectiveness of combined shockwave therapy and plantar stretching for plantar heel pain in adults will be included. Methods: The authors will search a wide range of sources to identify both published and unpublished studies via EBSCOhost, including, but not limited to MEDLINE, SPORTDiscus, CINAHL, Cochrane Central Register of Controlled Trials (CENTRAL), and Allied and Complementary Medicine Database (AMED). Studies published in a language other than English will only be considered if a translation is available. The JBI systematic review methodology will be followed when conducting the review. Data synthesis will be conducted using meta-analysis or narrative synthesis, where appropriate. Systematic review registration number: PROSPERO CRD42020171538